Exploring Patient Safety Risks in CAPD Services: A Qualitative Analysis Using Failure Mode and Effect Analysis (FMEA) - Pratiwi, Anggika Yelzi; Basabih, Masyitoh; Mulyani, Fifi (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2025)
Pasar Minggu Regional General Hospital is currently developing CAPD as a new service, which is a high-risk service involving healthcare professionals and patients themselves. This research aims to identify the risk of patient safety incidents using the FMEA method in CAPD at RSUD Pasar Minggu to prevent the incident risk. The research is qualitative research with an operational research approach. Data were obtained from primary sources through in-depth interviews and focus group discussion (FGD) and secondary data through a literature review. The result showed that the post-insertion process of peritoneal access and patient self-management in CAPD was the focus of the FMEA process. The priority risks were exit site/ tunnel infection, peritonitis infection, catheter obstruction, and leakage. The root cause of the risks is the incomplete CAPD service regulatory, education and re-education plans have not been implemented, and monitoring and evaluation have not been determined. Recommendations for preventing these risks include completing CAPD regulations in the service guidelines, optimizing patient education and re-education plans with CAPD training plan matrix and patient education poster, and establishing monitoring and evaluation procedures for CAPD patient care.